2009
DOI: 10.1517/17460440802661443
|View full text |Cite
|
Sign up to set email alerts
|

Polyether ionophores: broad-spectrum and promising biologically active molecules for the control of drug-resistant bacteria and parasites

Abstract: Background As multidrug-resistant (MDR) pathogens continue to emerge, there is a substantial amount of pressure to identify new drug candidates. Carboxyl polyethers, also referred to as polyether antibiotics, are a unique class of compounds with outstanding potency against a variety of critical infectious disease targets including protozoa, bacteria and viruses. The characteristics of these molecules that are of key interest are their selectivity and high potency against several MDR etiological agents. Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
137
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(153 citation statements)
references
References 157 publications
3
137
0
4
Order By: Relevance
“…In the 2D-ROESY spectrum, the correlations of the C-4-methoxy group with H-5, the C-6-methoxy group with H-4, and the coupling constant of H4 and H5 (J 4,5 ϭ 11.4) revealed that the C-4-methoxy group and H-5 were on one side of ring A, while the C-6-methoxy group and H-4 were on the opposite side. The ROE correlation of the C-16-methoxy group with H-17, H-17 with the C-20-methoxy group, and the C-20-methoxy group with H-21 revealed that they were on the same side of rings C, D, and E. Although 1 H-and 13 C-NMR data of C-25 were not identical to those of etheromycin, the coupling constants (J 24,25 and J 25,26 ) were similar to those of etheromycin, and a careful analysis of 2D-ROESY signals of ring F revealed that 1.264-B and etheromycin shared identical relative configurations of ring F. The coupling constants of H-4Ј and H-5Ј(J 4Ј,5Ј ϭ 9.0 or 10.8) of ring G inferred that they were on opposite sides of the ring, like etheromycin. Due to the existence of the C-8-methoxy group, the configuration of ring A of 1.264-B should be the same as that of etheromycin (40).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In the 2D-ROESY spectrum, the correlations of the C-4-methoxy group with H-5, the C-6-methoxy group with H-4, and the coupling constant of H4 and H5 (J 4,5 ϭ 11.4) revealed that the C-4-methoxy group and H-5 were on one side of ring A, while the C-6-methoxy group and H-4 were on the opposite side. The ROE correlation of the C-16-methoxy group with H-17, H-17 with the C-20-methoxy group, and the C-20-methoxy group with H-21 revealed that they were on the same side of rings C, D, and E. Although 1 H-and 13 C-NMR data of C-25 were not identical to those of etheromycin, the coupling constants (J 24,25 and J 25,26 ) were similar to those of etheromycin, and a careful analysis of 2D-ROESY signals of ring F revealed that 1.264-B and etheromycin shared identical relative configurations of ring F. The coupling constants of H-4Ј and H-5Ј(J 4Ј,5Ј ϭ 9.0 or 10.8) of ring G inferred that they were on opposite sides of the ring, like etheromycin. Due to the existence of the C-8-methoxy group, the configuration of ring A of 1.264-B should be the same as that of etheromycin (40).…”
Section: Resultsmentioning
confidence: 92%
“…1) are a unique class of type I polyketides with a high degree of promise for the control of drug-resistant bacteria and parasites, and they have been widely used as effective veterinary drugs and food additives in animal husbandry (13). These molecules also show a broad spectrum of bioactivity, including antifungal, antiviral, antitumor, herbicidal, and anti-inflammatory activity, as well as effects on the central nervous system (CNS) and immunoregulatory systems (24). The ability of polyethers to transport cations across plasma membranes leads to depolarization and succedent cell death.…”
mentioning
confidence: 99%
“…The ability of polyether ionophores to control drug-resistant bacteria and parasitic infections is well known, but these compounds also show a broad spectrum of bioactivities, including antifungal, antiviral, antitumor, herbicidal, and anti-inflammatory activities (58,59). In this study, a relatively high number of polyether-producing actinomycetes were isolated, notably the acidophilic streptomycetes (Streptomyces sp.…”
Section: Discussionmentioning
confidence: 97%
“…We succeeded to crystallizethe aforementioned natural product in the form of its methanol solvate. Dianemycin belongs to the class of carboxyl ionophores that complex the first row metal cations and therefore affect the transport of these latter in mitochondria [2]. This property results in outstanding activity against chloroquine-resistant forms of malaria.…”
mentioning
confidence: 99%